2015
DOI: 10.1007/s11104-015-2522-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epichloid endophytes and soil fertilization on arbuscular mycorrhizal colonization of a wild grass

Abstract: Background and aims Plants often establish multiple simultaneous symbiotic associations with different micro-organisms; however, the way in which each symbiont affects the other symbionts and the effects of these multiple interactions on plant performance are not well understood. The aim of this study was to evaluate how two different asexual Epichloë species modulate the establishment of arbuscular mycorrhizal fungi (AMF) in a wild forage grass under different soil fertilization levels. Methods We performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 53 publications
1
22
1
Order By: Relevance
“…However, asymptomatic endophyte and choke diseased plants differed in nutrients, fibers, and digestibility, indicating that Epichloë may affect aboveground, and possibly underground, processes involved in nutrient absorption. Vignale et al (2016) also worked on Epichloë species and evaluate how two different asexual species can modulate the establishment of arbuscular mycorrhizal fungi in a wild forage grass under different soil fertilization levels. The authors showed that endophyteinoculated plants produced more panicles than noninoculated plants.…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 99%
“…However, asymptomatic endophyte and choke diseased plants differed in nutrients, fibers, and digestibility, indicating that Epichloë may affect aboveground, and possibly underground, processes involved in nutrient absorption. Vignale et al (2016) also worked on Epichloë species and evaluate how two different asexual species can modulate the establishment of arbuscular mycorrhizal fungi in a wild forage grass under different soil fertilization levels. The authors showed that endophyteinoculated plants produced more panicles than noninoculated plants.…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 99%
“…Endophyte-infected grasses can also be infected with AMF simultaneously [64][65][66][67]. Studies show that endophyte infection can reduce the AMF colonization rates in tall fescue and perennial ryegrass [68][69][70]. Mack and Rudgers [65] further found that there was a negative correlation between the endophytic hyphae density in the leaf sheath of tall fescue and the colonization rate of AMF (Glomus intraradices).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Rojas et al (2016) found that E+ tall fescue regardless of CTE or NTE status increased relative abundance of the AMF phylum Glomeromycota via ITS1 rRNA sequencing but not the AMF lipid biomarker 16:1ω5cis in rhizosphere soil samples. Evaluation of other asexual Epichloë symbionts in cool-season grasses have similarly revealed negative (Müller, 2003; Liu et al, 2018), positive (Novas et al, 2005, 2009, 2011; Kazenel et al, 2015; Vignale et al, 2016), or mixed (Omacini et al, 2006; Liu et al, 2011; Larimer et al, 2012; Kalosa-Kenyon et al, 2018) effects on belowground AMF symbionts or microbial communities, with positive effects most prevalent in native or non-agronomic grasses. The inconsistencies described above highlight the need to better characterize the interactions between unique grass-endophyte combinations and belowground root symbionts, especially considering how new selected combinations are continually being developed and planted in agricultural grasslands.…”
Section: Introductionmentioning
confidence: 99%